PEMBUATAN HOTTEOK IKAN BANDENG DENGAN SUBSTITUSI TEPUNG RUMPUT LAUT SEBAGAI KUDAPAN KAYA PROTEIN - Hantoro, Hanifa Nuraini; Komariah, Kokom (Prosiding Pendidikan Teknik Boga Busana, 2025)
Hotteok is a typical South Korean snack made from wheat flour and glutinous rice flour. Filled with chopped nuts and brown sugar. This snack is usually sold in winter and served hot. The purpose of this research is to find the right recipe for making Milkfish Hotteok Fish recipe with seaweed flour substitution. The seaweed powder used in this study was Eucheuma cottonii seaweed. This study uses the Research & Development (R&D) research method with the 4D model. There are 3 percentages of seaweed flour substitution used, namely 5%, 10% and 20%. At the define stage, the researcher tested 3 reference recipes, which then selected one. At the design stage, the selected reference recipe will be substituted with seaweed flour with a presentation of 5%, 10% and 20%, then the best formula will be selected. Furthermore, at the develop stage, validation tests I and II are carried out for the product being developed. And the last stage, which is dissemination which is carried out at the culinary product exhibition and finding 50 panelists to carry out sensory tests. The results of the preference test used the Hedonic Scale Test analysis. From the research results, it can be seen that the difference between the reference product and the development in terms of color preference, taste, aroma, texture and overall properties.